Ricerca scientifica e dati genetici (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2022)
The paper aims to study the relationship between scientific research and protection of fundamental right of the human being. In particular, it focuses on the concern linked to the use of the genetic data in the field of the predictive medicine and discusses how current legal frameworks and technical safeguards can mitigate the risks connected to new technologies, artificial intelligence, and digital communication.